Opportunities and Challenges of Marine Logistics Policy in Supporting Blue Economy - Muammar Kadhafi (Collaborate Engineering Daily Book Series, 2024)
The blue economy has become an important concept in sustainable development, with maritime logistics playing an important role in supporting blue economy sectors. This research aims to explore the opportunities and challenges in implementing maritime logistics policies to support the blue economy. The research methods used include literature studies, policy analysis, case studies, surveys, and data triangulation. The research results identify key opportunities from maritime logistics policies in supporting the blue economy, such as economic growth, global market connectivity, infrastructure investment, job creation, and marine environmental preservation. However, there are significant challenges that need to be overcome, such as coordination between stakeholders, lack of adequate infrastructure, lack of skilled human resources, a regulatory framework that is not yet fully supportive, and funding challenges. The proposed policy recommendations include increasing coordination between stakeholders, sustainable infrastructure investment, human resource development, strengthening the regulatory framework, and innovative funding schemes. This research provides valuable insights for policy makers, industry players, academics, and other stakeholders in efforts to develop effective maritime logistics policies to support the blue economy sustainably.